Performing pregnancy: Comic content, critique and ambivalence in pregnant stand-up comedy. (May 2023) - Lockyer, Sharon; De Benedictis, Sara
Stand-up comedy has recently become a primary site where representations of pregnancy are increasingly prevalent. Yet little academic work focuses on pregnant stand-up comedians and their performances. Taking an interdisciplinary approach, this article examines the cultural work of pregnant stand-up comedy. Thematic analysis of pregnant stand-up comedy by Amy Schumer, Ellie Taylor and Ali Wong identifies three significant features characterising the performances: (1) Comedic Corporeality, Vulgarity and Ambiguity; (2) Breaking Silences through the 'Unruly Expectant Mother'; and (3) Critiquing Maternity Inequality through Pregnant Stand-Up? We examine how pregnant stand-up comedy interacts with and disrupts dominant cultural pregnancy representations, illustrating how pregnancy functions simultaneously as comic content and critique in the performances. Such comic content and critique are characterised by complexity as ambivalence is central to pregnant stand-up comedy. We argue it is precisely such ambivalence that provides productive means to understand the cultural and theoretical significances of pregnant stand-up comedy.